Optimasi Konsentrasi Paklobutrazol untuk Respons Pembungaan Tanaman Jambu Biji 'Kristal' - Siti Sarah Yutamimah; R. A. Diana Widyatuti; Setyo Dwi Utomo; Yohannes Cahya Ginting (Universitas Lampung, 2023)
The advantages of 'Crystal' guava in Indonesia provide opportunities for farmers to cultivate and increase their production. Various methods of cultivation have been developed to increase the production of 'Crystal' guava, one of which is the use of Growth Regulators. Paclobutrazol is a plant PGR that regulates flowering outside the harvest season so that the production of 'Crystal' guava fruit can be maintained. The purpose of this study was to determine the best concentration of the effect of Paclobutrazol treatment in increasing the flowering of 'Crystal' guava plants. The research was conducted from August 2021 to March 2022 in Rajabasa Lama 1 Village, Labuhan Ratu District, East Lampung Regency. The treatment was carried out in a factorial manner using a single factor randomized block design with three replications so that 36 experimental units were obtained. The first factor was Paclobutrazol (A) which consisted of 6 treatment levels, there are A1 (0 ppm), A2 (4000 ppm), A3 (6000 ppm), A4 (8000 ppm), A5 (10,000 ppm), A6 (12,000 ppm). Paclobutrazol treatment with a concentration of 10,000 ppm gave the best results on the variables of flower number, number of ovules, number of harvested fruit and weight of harvested fruit. Keywords : Paclobutrazol, Concentration, ‘Crystal’ Guava Plants